Flexammina islandica gen. nov. sp. nov. and some new phylotypes of monothalamous foraminifera from the coast of Iceland - Voltski, Ivan; Pawlowski, Jan (Zootaxa, 2015)
Monothalamous (single-chambered) foraminifera comprise a poorly known group, the diversity of which is strongly underestimated according to environmental DNA surveys. The gross morphology of monothalamids offers few distinguishing features; their organic-walled or agglutinated tests are often very delicate and make isolation difficult. Here, we use an integrated taxonomic approach, including morphological and molecular analysis, to examine the diversity of monothalamids in a shallow subtidal area on the coast of Iceland. We report nine new phylotypes of single-chambered foraminifera distinguished by SSU rDNA sequences. Among them, we establish a new genus Flexammina and a new species Flexammina islandica, possessing a very pliable, finely agglutinated test capable of extreme shape transformations. According to molecular data, F. islandica belongs to the monothalamid clade M, which also includes the well-known genus Allogromia. In addition, we provide brief descriptions and illustrations of nine other monothalamous foraminifera isolated from the same area. Three of them are closely related to some unidentified environmental sequences and serve as the first microscopic documentation of these anonymous lineages.